Analysis of the current state of the textile industry of Uzbekistan - Abdullaeva Sevarakhon Khasanovna (International Journal on Orange Technologies, 2021)
Light industry is one of the leading branches of the global industrial complex. It accounts for about 6% of the world's GDP and more than 14% of those employed in the industrial complex. As a strategic sector for the economy of Uzbekistan, light industry provides a high level of employment, contributes to the economic and industrial potential and the international prestige of the country. According to its importance, it is necessary to analyze the production process and determine the main obstacles to development. In article the analysis of a state condition of textile industry of Uzbekistan is carried out. According to the results of the analysis the main directions of the development of the sphere are determined